Penyuluhan Bahaya Pergaulan Bebas dikalangan Masyarakat Kelurahan Gurun Panjang - Khairul Amri; Anisa Ramdhani; Vicka Putria Herlina; Revandi Jansah; Dea Valenda Syadhani; Dewi Kartika Sari; Mhd. Qur’anil Hasan; Putri Rindiani M. Bakara; Berliana Bertuah Lubis; Kevin Christian Sion; Anisa Putri Zalya (LP2M Universitas Muhammadiyah Enrekang, 2023)
Promiscuity among society is a phenomenon that is increasingly common in everyday life. Promiscuity causes serious negative impacts, especially among teenagers. The problem found in Gurun Panjang Subdistrict is that there is still promiscuity among the people of Gurun Panjang. So the aim of this service activity includes increasing public knowledge about the dangers of promiscuity and helping motivate the community, especially teenagers in Gurun Panjang Subdistrict, to stay away from promiscuity. Implementation of community service regarding the dangers of promiscuity is carried out by conducting outreach or outreach to the community and the technique for implementing the outreach program is carried out using outreach teaching aids in the form of poster leaflets to village communities accompanied by questions and answers directly at the location. Where the result of the service carried out is the promiscuity among the community that is most often done in Gurun Panjang Subdistrict currently is drinking alcohol. Therefore, Kukerta students at the University of Riau provide outreach or education regarding the dangers of promiscuity using poster media. Where Kukerta students provide knowledge and explanations regarding the impacts caused by free association.